Marketability Study of Mathematical Sciences Students in Universiti Kebangsaan Malaysia (UKM) - Lim Chui Ting; Ong Wen Xuan; Muhammad Aris Fadzilah, Nurulain Nabilah Binti; Nora Binti Muda (Enthusiastic : International Journal of Applied Statistics and Data Science, 2023)
Higher Education Institute (HEI) has a vital role in developing human capital of a country. Measuring the quality of teaching and learning system in HEI and also industry’s satisfaction level is important to ensure the marketability of HEI graduates. This study examined Universiti  Kebangsaan Malaysia (UKM) Mathematical Sciences students’ marketability by determining industry’s satisfaction level on students’ skills and abilities during industrial training and identifies factors that affect students’ marketability. There were 22 student attributes that were categorized into four factors. Mean scores and Relative Importance Analysis determined the satisfaction and importance level of each attribute studied respectively. Besides, Penalty-Reward Contrast Analysis (PRCA) showed that affective factor was categorized as a basic factor where its existence did not increase but its absence decreased the industry’s satisfaction level. For Importance Performance Analysis (IPA), cognitive, affective, and cognitive & psychomotor factors were observed in the first quadrant which had high importance level but low performance level. Lastly, all four factors were found in the loyal customer zone and at an excellent level through Customer Satisfaction Index (CSI) analysis. In conclusion, UKM Mathematical Sciences students have high marketability in general, but preservation and improvement should be implemented on important attributes to enhance their marketability.